Magnetic toy ingestion leading to jejunocecal fistula in a child - Ahmed, Ali M; Hassab, Mohamed H; Al-Hussaini, Abdulrahman A; Al-Tokhais, Tariq I (Saudi medical journal, 2010)
The accidental ingestion of a foreign body is a common problem in children, but ingestion of magnets is rare. When multiple magnets are ingested, they may attract each other and cause pressure necrosis through the bowel walls and eventually lead to serious complications like obstruction, perforation, and fistula formation. We report a case of a 5-year-old girl with jejunocecal fistula following ingestion of 2 magnet toys; it highlights the diagnostic challenge and the need for early surgical intervention in children especially when multiple magnets are ingested.